A Scoping Review of Predictive Analytics for Enhancing Resource Efficiency in Business Operations (OCEM Journal of Management, Technology & Social Sciences, 2026)
In the wake of the digital era, intense competition, globalization, fast-paced technological advancements and growing cost challenges; businesses are essential to making accurate predictions, maximization of operations, and optimizing resource consumption for sustainable operations. Predictive Analytics (PA) offers possibilities to proactively predict outcomes based on historical data and analytics to identify patterns. PA has the potential to revolutionize the front-end, middle and back-end business operations in view of achieving the maximum use of resources.With applications in finance, health, retail, and the automobile industry, the spillover literature to explore the influence of Predictive Analytics in the context of resource efficiency of business operations is scarce. By using the scoping review method, this paper aims to collect and analyze the current state of the art on the influence and effect of Predictive Analytics in order to provide theoretical and practical implications, action agendas for future research, and assist the making of informed policy decisions.